FDI DAN INFLASI MEMPENGARUHI PERTUMBUHAN INDUSTRI KOSMETIK DI INDONESIA - Ratih Ikha Permata Sari (JABE (Journal of Applied Business and Economic), 2022)
This study aims to analyze the growth factors of the cosmetic industry in Indonesia. The economic variables analyzed were FDI and inflation as independent variables. Meanwhile, the growth of the cosmetic industry is the dependent variable. The data used is secondary data from five companies, namely PT. Paragon Technology and Innovation, Marthatilaaar Group, Viva Cosmetics, PT. Mustika Ratu and LOREAL, during the period 2010-2021. This research is a quantitative research, which is to explain statistically the relationship and influence of economic variables on the growth of the cosmetic industry in Indonesia, both in whole and in part. The data analysis technique used is multiple linear regression with panel data. The results showed that FDI had a significant effect while inflation had no effect on the growth of the cosmetics industry. This is indicated by the value of F-statistics 424.2280 > F-table and prob (F-statistics) of 0.000000 <0.05. Partially FDI has a significant effect on the growth of the cosmetic industry where the t-statistic value is 28.82672 < t-table value 1.70 and the prob value (t-statistic) is 0.0000 > 0.05. Meanwhile, inflation has no effect on the growth of the cosmetic industry on economic growth, where the t-statistic value is 0.950083 < t-table value 1.70 and the prob value (t-statistic) is 0.3431 > 0.05.